If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(w + 3) + 4w = 0 Reorder the terms: 2(3 + w) + 4w = 0 (3 * 2 + w * 2) + 4w = 0 (6 + 2w) + 4w = 0 Combine like terms: 2w + 4w = 6w 6 + 6w = 0 Solving 6 + 6w = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 6w = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 6w = 0 + -6 6w = 0 + -6 Combine like terms: 0 + -6 = -6 6w = -6 Divide each side by '6'. w = -1 Simplifying w = -1
| 6m/6n | | y-8=(-7/9)*18 | | -2(x+3)+4w= | | 28/e=7/14 | | 9a+18+15=33 | | y-8=(-7/9)x | | 64+4y=-4y | | 11x=10x | | 5/y=15/60 | | d/60=40/10 | | 1/2h(11)=33 | | 10g-7=73 | | 10-7=73 | | 31=3y-8 | | -27=3(y-3)-6y | | 5x-5=10-5x | | 40/100=x/552 | | -27=3 | | 2.2-0.35= | | 37/7=25/x | | x+.40x=40000 | | 3x=11000 | | (2*b+4)+(b+7)=4b | | -3(x+1)=-12 | | 3x+44-3=0 | | -9=4b | | 4b=-9 | | b+7=0 | | 5(x-3)=2(3x-10) | | 4v=54 | | 12x=15-3y | | 2lnx-ln(2x)=2 |